A high thermal conductivity and corrosion resistant magnesium alloy and its preparation method
By adding Nd and Sc to magnesium alloys to form a dense film and a low potential difference precipitate, and combining this with a simple smelting process, the problem of magnesium alloys being unable to simultaneously achieve high thermal conductivity and high corrosion resistance was solved, and a high thermal conductivity and corrosion resistant magnesium alloy that meets the requirements of electronic products was prepared.
Patent Information
- Application Number
- CN202311375000.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2025-11-14
- Estimated Expiration
- 2043-10-23
AI Technical Summary
Existing magnesium alloys cannot simultaneously achieve both high thermal conductivity and high corrosion resistance, thus failing to meet the requirements for use in electronic products.
Magnesium alloys are prepared by adding 1-5% Nd and 0.05-0.1% Sc to magnesium alloys to form a dense film to improve corrosion resistance, and by reducing the tendency of microgalvanic corrosion through the Mg12Nd precipitate formed by Nd and Mg, while controlling the content of impurity Fe. The process is combined with simple smelting and casting.
The thermal conductivity of magnesium alloys reached 75-100 W/(m*K), while the corrosion rate in Cl- containing solution reached 0.15-0.4 mm/y, exhibiting good thermal conductivity and corrosion resistance, thus meeting the performance requirements of electronic products.
Smart Images

Figure CN117778847B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a magnesium alloy, and more particularly to a magnesium alloy with both high thermal conductivity and high corrosion resistance, and a method for preparing the same. Background Technology
[0002] Magnesium alloys, as a crucial structural material in the lightweight revolution, have broad development prospects. The 3C industry focuses on the portability of its products, and magnesium alloys, due to their ease of forming, high specific strength, and superior surface treatment methods, have received widespread attention in this sector. However, the poor corrosion resistance of magnesium alloys limits the service life of products in use, significantly restricting their further widespread application. On the other hand, with the continuous improvement of electronic product performance, heat dissipation has become a major challenge in realizing a revolution in the magnesium alloy industry.
[0003] Generally, thermal conductivity increases with the amount of precipitated phase. However, on the other hand, as the number of precipitated phases increases, microgalvanic corrosion also intensifies, making it difficult to achieve both high thermal conductivity and high corrosion resistance. Existing magnesium alloys are generally unable to achieve a balance between high thermal conductivity and high corrosion resistance, thus failing to meet current application requirements. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a magnesium alloy that combines high thermal conductivity and high corrosion resistance. Furthermore, this invention also provides a method for preparing the said magnesium alloy.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a high thermal conductivity and corrosion resistant magnesium alloy, wherein the magnesium alloy contains the following components by weight percentage: Nd 1-5%, Sc 0.05-0.1%, and the balance being Mg and unavoidable impurities.
[0006] The magnesium alloy of the present invention contains 1-5% by mass Nd, wherein the PBR of the Nd hydroxide is greater than 1. When the magnesium alloy is placed in a Cl-containing environment... - In solution, Nd can effectively form a dense film, thereby improving the corrosion resistance of magnesium alloys. Meanwhile, due to its half-filled 4f4 orbitals, Nd contributes significantly to thermal conductivity, resulting in Mg12Nd with Mg, which exhibits good thermal conductivity and has a low formation energy, making it readily precipitated in the matrix. Furthermore, the electrode potential of Nd is closer to that of Mg, and the potential difference between the precipitated phase and the matrix differs from that of conventional precipitates, such as Mg17Al12, which has a potential difference of up to 150 mV, forming a strong micro-couple. The potential difference between the Mg12Nd precipitate and the matrix is lower, around 10 mV, making micro-couple corrosion less pronounced.
[0007] Meanwhile, the magnesium alloy of the present invention also contains 0.05-0.1% Sc by mass, which can further and effectively improve the corrosion resistance of the magnesium alloy. Moreover, although Sc is expensive, it has a strong tendency to accelerate the formation of Mg(OH)2, so adding a small amount of Sc can significantly accelerate the densification process of the film and improve the corrosion resistance.
[0008] Through repeated experiments and research, the inventors of this application discovered that when the magnesium alloy contains Nd, Sc and Mg ternary components within the specified content range, the components work together to enable the magnesium alloy to simultaneously achieve high thermal conductivity and high corrosion resistance, thus better meeting the performance requirements in current applications.
[0009] In a preferred embodiment of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention, the Nd content in the magnesium alloy is 2-3% by mass.
[0010] In a preferred embodiment of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention, the Nd content in the magnesium alloy is 2.5% by mass.
[0011] In a preferred embodiment of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention, the mass percentage of Sc in the magnesium alloy is 0.06 to 0.08%.
[0012] In a preferred embodiment of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention, the mass percentage of Sc in the magnesium alloy is 0.07%.
[0013] In a preferred embodiment of the high thermal conductivity and corrosion-resistant magnesium alloy of the present invention, the magnesium alloy comprises the following components by weight percentage: Nd 2.78%, Sc 0.07%, with the balance being Mg and unavoidable impurities. When the magnesium alloy contains the specific proportions of these components, the thermal conductivity of the magnesium alloy can reach 98 W / (m*K), while the content of Cl... - The corrosion rate in the solution can reach 0.15 mm / y, and it has good thermal conductivity and corrosion resistance.
[0014] In a preferred embodiment of the high thermal conductivity and corrosion-resistant magnesium alloy of the present invention, the magnesium alloy comprises the following components by weight percentage: Nd 2.31%, Sc 0.06%, with the balance being Mg and unavoidable impurities. When the magnesium alloy contains the specific proportions of the components described above, the thermal conductivity of the magnesium alloy can reach 80 W / (m*K), and the corrosion rate in Cl- containing solution can reach 0.23 mm / y, exhibiting good thermal conductivity and corrosion resistance.
[0015] In a preferred embodiment of the high thermal conductivity and corrosion-resistant magnesium alloy of the present invention, the unavoidable impurities contain Fe, and the mass percentage of Fe in the magnesium alloy is not higher than 0.05%. In the magnesium alloy described in this application, it is necessary to control the mass percentage of Fe in the unavoidable impurities to not exceed 0.05%. If the Fe content is too high, it will lead to severe microgalvanic corrosion, causing a decrease in corrosion resistance. It will also lead to a decrease in thermal conductivity.
[0016] In a preferred embodiment of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention, the thermal conductivity of the magnesium alloy is 75-100 W / (m*K).
[0017] As a preferred embodiment of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention, the corrosion rate of the magnesium alloy in Cl- containing solution is 0.15 to 0.4 mm / y.
[0018] The magnesium alloy described in this invention has a thermal conductivity of 75-100 W / (m*K) and a corrosion rate of 0.15-0.4 mm / y in Cl- solution, exhibiting both high thermal conductivity and good corrosion resistance.
[0019] Meanwhile, another objective of this invention is to provide a simple process for preparing the aforementioned high thermal conductivity and corrosion-resistant magnesium alloy, which is conducive to industrial application. To achieve this objective, the technical solution adopted by this invention is as follows: a method for preparing the aforementioned high thermal conductivity and corrosion-resistant magnesium alloy, the method comprising the following steps:
[0020] (1) Based on the composition of the magnesium alloy, calculate the required amount of pure magnesium, magnesium-neodymium master alloy, and magnesium-scandium master alloy, and carry out material preparation and preheating treatment of the alloy and mold.
[0021] (2) In the presence of a protective gas, pure magnesium ingots, magnesium-neodymium master alloys and magnesium-scandium master alloys are melted to obtain magnesium alloy melt;
[0022] (3) In the presence of a protective gas, the magnesium alloy melt is subjected to stirring, refining, static heat preservation and slag removal in sequence to obtain a purified magnesium alloy melt.
[0023] (4) In the presence of a protective gas, the purified magnesium alloy melt is cast into a preheated metal mold to prepare a magnesium alloy.
[0024] In a preferred embodiment of the preparation method of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention, the protective gas in steps (2) to (4) is a mixture of SF6 and CO2.
[0025] In a preferred embodiment of the preparation method of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention, the melting temperature in step (2) is 720°C and the time is 30 min.
[0026] As a preferred embodiment of the preparation method of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention, the refining temperature in step (3) is 750°C and the time is 10 min; the temperature for static heat preservation is 730°C and the time is 30 min.
[0027] In a preferred embodiment of the preparation method of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention, the casting temperature in step (4) is 720°C.
[0028] The magnesium alloy of this invention, by adding a certain amount of Nd element, wherein the PBR of the Nd element hydroxide is greater than 1, when the magnesium alloy is placed in a Cl-containing environment... - In solution, it can effectively form a dense film, thereby improving the corrosion resistance of magnesium alloys. Simultaneously, the inventors of this application discovered that the Nd element has a half-filled 4f4 orbital configuration, which significantly improves the thermal conductivity of magnesium alloys. It can form Mg12Nd with Mg, exhibiting good thermal conductivity, and has a low formation energy, making it easy to precipitate in the matrix. Furthermore, the inventors of this application also discovered that because the electrode potential of Nd is closer to that of Mg, the potential difference between its precipitated phase and the matrix differs from that of conventional precipitated phases, such as Mg17Al12, which has a potential difference of up to 150mV with the matrix, forming a strong micro-couple pair. The potential difference between the Mg12Nd precipitated phase and the matrix is as low as 10mV, resulting in a less pronounced tendency for micro-couple corrosion. In addition, the magnesium alloy also contains a small amount of Sc element; the addition of a small amount of Sc element, in conjunction with the Nd element, can significantly improve the corrosion resistance of the magnesium alloy. The magnesium alloy described in this invention exhibits a thermal conductivity of 75–100 W / (m*K) and a corrosion rate of 0.15–0.4 mm / y in Cl--containing solutions, thus simultaneously achieving both high thermal conductivity and high corrosion resistance, better meeting current application requirements. The preparation method of the magnesium alloy described in this invention involves simple process steps, facilitating industrial application and enabling rapid and efficient preparation of the magnesium alloy with the properties described herein. Attached Figure Description
[0029] Figure 1 Scanning electron microscope image of the magnesium alloy described in Example 1;
[0030] Figure 2 This is a potential difference test diagram of the magnesium alloy described in Example 1;
[0031] Figure 3 Corrosion morphology of the magnesium alloy described in Comparative Example 1;
[0032] Figure 4The images show the corrosion film defects of Example 1 and Comparative Examples 1-3. Detailed Implementation
[0033] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0034] Example 1
[0035] An embodiment of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention comprises the following components by weight percentage: Nd 2.78%, Sc 0.07%, with the balance being Mg and unavoidable impurities; the unavoidable impurities contain Fe, and the Fe content in the magnesium alloy is 0.038% by weight.
[0036] The high thermal conductivity and corrosion-resistant magnesium alloy described in this embodiment is prepared using the following method:
[0037] (1) Weigh out pure magnesium, Mg30Nd and Mg30Sc respectively, and prepare materials and preheat the alloy and mold; the pure magnesium is 2610g, the Mg30Nd is 430g and the Mg30Sc is 30g;
[0038] (2) Under the protection of SF6 and CO2 mixed gas, pure magnesium ingots, Mg30Nd and Mg30Sc were melted at a melting temperature of 720℃ for 30 min to obtain magnesium alloy melt;
[0039] (3) Under the protection of SF6 and CO2 mixed gas, the magnesium alloy melt is subjected to stirring, refining, static heat preservation and slag removal treatment in sequence. The refining temperature is 750℃, the refining time is 10min, the static heat preservation temperature is 730℃, and the static heat preservation time is 30min to obtain purified magnesium alloy melt.
[0040] (4) Under the protection of SF6 and CO2 mixed gas, the purified magnesium alloy melt is cast into a preheated metal mold at a temperature of 720°C to prepare magnesium alloy.
[0041] Example 2
[0042] An embodiment of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention comprises the following components by weight percentage: Nd 2.31%, Sc 0.06%, with the balance being Mg and unavoidable impurities; the unavoidable impurities contain Fe, and the Fe content in the magnesium alloy is 0.035% by weight.
[0043] The only difference between the preparation method of the high thermal conductivity and corrosion resistant magnesium alloy described in this embodiment and that in Example 1 is the amount of pure magnesium, Mg30Nd, and Mg30Sc added. In the preparation process of this embodiment, the amount of pure magnesium, Mg30Nd, and Mg30Sc is calculated based on the composition content of the magnesium alloy described in this embodiment. Other process steps and parameters are the same as in Example 1.
[0044] Example 3
[0045] An embodiment of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention comprises the following components by weight percentage: Nd 2.5%, Sc 0.08%, with the balance being Mg and unavoidable impurities; the unavoidable impurities contain Fe, and the Fe content in the magnesium alloy is 0.04% by weight.
[0046] The only difference between the preparation method of the high thermal conductivity and corrosion resistant magnesium alloy described in this embodiment and that in Example 1 is the amount of pure magnesium, Mg30Nd, and Mg30Sc added. In the preparation process of this embodiment, the amount of pure magnesium, Mg30Nd, and Mg30Sc is calculated based on the composition content of the magnesium alloy described in this embodiment. Other process steps and parameters are the same as in Example 1.
[0047] Example 4
[0048] An embodiment of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention comprises the following components by weight percentage: Nd 3%, Sc 0.07%, with the balance being Mg and unavoidable impurities; the unavoidable impurities contain Fe, and the Fe content in the magnesium alloy is 0.045% by weight.
[0049] The only difference between the preparation method of the high thermal conductivity and corrosion resistant magnesium alloy described in this embodiment and that in Example 1 is the amount of pure magnesium, Mg30Nd, and Mg30Sc added. In the preparation process of this embodiment, the amount of pure magnesium, Mg30Nd, and Mg30Sc is calculated based on the composition content of the magnesium alloy described in this embodiment. Other process steps and parameters are the same as in Example 1.
[0050] Example 5
[0051] An embodiment of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention comprises the following components by weight percentage: Nd 2%, Sc 0.05%, with the balance being Mg and unavoidable impurities; the unavoidable impurities contain Fe, and the Fe content in the magnesium alloy is 0.042% by weight.
[0052] The only difference between the preparation method of the high thermal conductivity and corrosion resistant magnesium alloy described in this embodiment and that in Example 1 is the amount of pure magnesium, Mg30Nd, and Mg30Sc added. In the preparation process of this embodiment, the amount of pure magnesium, Mg30Nd, and Mg30Sc is calculated based on the composition content of the magnesium alloy described in this embodiment. Other process steps and parameters are the same as in Example 1.
[0053] Example 6
[0054] An embodiment of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention comprises the following components by weight percentage: Nd 1%, Sc 0.1%, with the balance being Mg and unavoidable impurities; the unavoidable impurities contain Fe, and the Fe content in the magnesium alloy is 0.046% by weight.
[0055] The only difference between the preparation method of the high thermal conductivity and corrosion resistant magnesium alloy described in this embodiment and that in Example 1 is the amount of pure magnesium, Mg30Nd, and Mg30Sc added. In the preparation process of this embodiment, the amount of pure magnesium, Mg30Nd, and Mg30Sc is calculated based on the composition content of the magnesium alloy described in this embodiment. Other process steps and parameters are the same as in Example 1.
[0056] Example 7
[0057] An embodiment of the high thermal conductivity and corrosion resistant magnesium alloy of the present invention comprises the following components by weight percentage: Nd 5%, Sc 0.09%, with the balance being Mg and unavoidable impurities; the unavoidable impurities contain Fe, and the Fe content in the magnesium alloy is 0.05% by weight.
[0058] The only difference between the preparation method of the high thermal conductivity and corrosion resistant magnesium alloy described in this embodiment and that in Example 1 is the amount of pure magnesium, Mg30Nd, and Mg30Sc added. In the preparation process of this embodiment, the amount of pure magnesium, Mg30Nd, and Mg30Sc is calculated based on the composition content of the magnesium alloy described in this embodiment. Other process steps and parameters are the same as in Example 1.
[0059] Comparative Example 1
[0060] This comparative example provides a magnesium alloy comprising the following components by weight percentage: 2.78% Nd, with the balance being Mg and unavoidable impurities; the unavoidable impurities include Fe, and the Fe content in the magnesium alloy is 0.042% by weight.
[0061] The difference between this comparative example and Example 1 is that it does not contain Sc, but the process steps and conditions are the same.
[0062] Comparative Example 2
[0063] This comparative example provides a magnesium alloy comprising the following components by weight percentage: 0.07% Sc, with the balance being Mg and unavoidable impurities; the unavoidable impurities include Fe, and the Fe content in the magnesium alloy is 0.047% by weight.
[0064] The difference between this comparative example and Example 1 is that it does not contain Nd, but the process steps and conditions are the same.
[0065] Comparative Example 3
[0066] This comparative example provides a magnesium alloy comprising the following components by weight percentage: 6% Nd, 0.09% Sc, with the balance being Mg and unavoidable impurities; the unavoidable impurities include Fe, and the Fe content in the magnesium alloy is 0.044% by weight.
[0067] The difference between this comparative example and Example 1 is that the Nd content is increased, while the process steps and conditions are the same.
[0068] Example 1
[0069] Thermal conductivity and corrosion resistance tests of the magnesium alloy described in this invention
[0070] Magnesium alloys from Examples 1-7, magnesium alloys from Comparative Examples 1-7, and magnesium alloy AZ91D were used as test objects. The thermal conductivity and corrosion resistance of each group of magnesium alloys were tested, and the test methods are as follows:
[0071] Thermal conductivity: The results were obtained by testing and calculation using an LFA467 laser thermal conductivity meter in accordance with ASTM E1269-11, "Standard Test Method for Determination of Specific Heat Capacity by Differential Scanning Calorimetry".
[0072] Q = C p ×ρ×D
[0073] Where C p ρ is the specific heat capacity of the material, D is the thermal diffusivity, and Q is the thermal conductivity.
[0074] Corrosion resistance: Tested and calculated on an autolab 300 according to GBT 24196-2009 "Corrosion of metals and alloys, electrochemical test methods, guide for measurement of potentiostatic and potentiodynamic polarization".
[0075]
[0076] Where ρ is the material density, i is the measured corrosion current density, E is the electrochemical equivalent, and v is the corrosion rate.
[0077] The results are shown in Table 1.
[0078] Table 1. Test results of thermal conductivity and corrosion rate of magnesium alloys in each group.
[0079]
[0080]
[0081] As shown in Table 1, the magnesium alloy obtained in this invention, through adjustment of the elemental formulation, significantly improves its thermal conductivity and effectively reduces its corrosion rate in Cl--containing solutions. It achieves a balance between thermal conductivity and corrosion resistance, exhibiting excellent overall performance. In contrast, Comparative Examples 1-3 and magnesium alloy AZ91D suffer from insufficient thermal conductivity or excessively rapid corrosion, failing to achieve the desired balance between thermal conductivity and corrosion resistance.
[0082] Example 2
[0083] (1) Scanning electron microscopy results
[0084] Using the magnesium alloy described in Example 1 as the test object, electron microscopy was performed on the magnesium alloy described in Example 1, and the electron micrographs are attached. Figure 1 As shown. (Attached) Figure 1 In the image, the black portion represents the magnesium alloy matrix phase, which is the precipitated phase. The network-like distribution of the second phase forms a corrosion barrier, improving the corrosion resistance of the matrix. Simultaneously, the strip-shaped precipitated phase acts as a thermally conductive phase, enhancing its thermal conductivity.
[0085] (2) Potential difference test
[0086] Using the magnesium alloy described in Example 1 as the test object, the potential difference between the precipitated phase and the matrix of the magnesium alloy described in Example 1 was tested according to GB / T 24196-2009 "Corrosion of metals and alloys - Electrochemical test methods - Guidelines for measurement of potentiostatic and potentiodynamic polarization". The test results are attached. Figure 2 As shown. (From the appendix) Figure 2 The results show that the potential difference between the precipitated phase and the potential site is small.
[0087] (3) Corrosion morphology
[0088] The corrosion morphology of the magnesium alloy matrix described in Comparative Example 1 after corrosion is shown in the attached figure. Figure 3 As shown. (From the appendix) Figure 3 It can be seen that there are severe corrosion marks on its surface;
[0089] The corrosion film defects of Example 1 were compared with those of Comparative Examples 1-3, as shown in the appendix. Figure 4 As shown, by detecting the number of defects in the corrosion film using CT, it can be found that the addition of appropriate amounts of Nd and Sc significantly reduces the number of defects in the film.
[0090] The electron microscopy scans and potential differences of the other embodiments show similar results to those of Example 1. The corrosion morphology of the other embodiments and comparative examples also shows similar results to those of Example 1 and Comparative Examples 1 to 3, and will not be described again here.
[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A high thermal conductivity and corrosion-resistant magnesium alloy, characterized in that, The magnesium alloy is composed of the following components by weight percentage: Nd 2-3%, Sc 0.06-0.08%, with the balance being Mg and unavoidable impurities; The unavoidable impurities contain Fe, and the mass percentage of Fe in the magnesium alloy is not higher than 0.05%. The magnesium alloy has Mg12Nd precipitates; The thermal conductivity of the magnesium alloy is 75~100 W / (m*K). The magnesium alloy contains Cl... - The corrosion rate in the solution is 0.15~0.4 mm / y; The preparation method of the high thermal conductivity and corrosion resistant magnesium alloy includes the following steps: (1) Calculate the required amount of pure magnesium, magnesium-neodymium master alloy, and magnesium-scandium master alloy based on the composition content of the magnesium alloy, and carry out material preparation and preheating treatment of the alloy and mold. (2) In the presence of a protective gas, pure magnesium ingots, magnesium-neodymium master alloys, and magnesium-scandium master alloys are melted to obtain a magnesium alloy melt; (3) In the presence of a protective gas, the magnesium alloy melt is subjected to stirring, refining, static heat preservation and slag removal in sequence to obtain a purified magnesium alloy melt. (4) In the presence of a protective gas, the purified magnesium alloy melt is cast into a preheated metal mold to prepare a magnesium alloy.
2. The high thermal conductivity and corrosion-resistant magnesium alloy as described in claim 1, characterized in that, The Nd content in the magnesium alloy is 2.5% by mass.
3. The high thermal conductivity and corrosion-resistant magnesium alloy as described in claim 1, characterized in that, The Sc content in the magnesium alloy is 0.07% by mass.
4. The high thermal conductivity and corrosion-resistant magnesium alloy as described in claim 1, characterized in that, The magnesium alloy is composed of the following components by weight percentage: Nd 2.78%, Sc 0.07%, with the balance being Mg and unavoidable impurities; Alternatively, the magnesium alloy may be composed of the following components by weight percentage: Nd 2.31%, Sc 0.06%, with the balance being Mg and unavoidable impurities.
5. The method for preparing the high thermal conductivity and corrosion-resistant magnesium alloy according to any one of claims 1 to 4, characterized in that, The method includes the following steps: (1) Calculate the required amount of pure magnesium, magnesium-neodymium master alloy, and magnesium-scandium master alloy based on the composition content of the magnesium alloy, and carry out material preparation and preheating treatment of the alloy and mold. (2) In the presence of a protective gas, pure magnesium ingots, magnesium-neodymium master alloys, and magnesium-scandium master alloys are melted to obtain a magnesium alloy melt; (3) In the presence of a protective gas, the magnesium alloy melt is subjected to stirring, refining, static heat preservation and slag removal in sequence to obtain a purified magnesium alloy melt. (4) In the presence of a protective gas, the purified magnesium alloy melt is cast into a preheated metal mold to prepare a magnesium alloy.
6. The method for preparing the high thermal conductivity and corrosion-resistant magnesium alloy as described in claim 5, characterized in that, The preparation method shall satisfy at least one of the following: (a) The protective gas in steps (2) to (4) is a mixture of SF6 and CO2; (b) The melting temperature in step (2) is 720°C and the melting time is 30 min; (c) In step (3), the refining temperature is 750℃ and the time is 10 min; the temperature for standing and holding is 730℃ and the time is 30 min; (d) The casting temperature in step (4) is 720℃.
Citation Information
Patent Citations
Corrosion-resistant magnesium alloy and preparation method thereof
CN115852224A
Magnesium alloy having excellent mechanical properties and corrosion resistance, and method for manufacturing same
WO2017116020A1